CHINA'S RISE: SHAPING A MULTIPOLAR WORLD THROUGH PEACEFUL ECONOMIC GROWTH - Asghar Raza Burfat; Hans Raj; Bakhtawar Talpur (Journal of Religion and Society, 2024)
China’s unprecedented economic growth over the past few decades has been both rapid and transformative, positioning it as a key architect of a multipolar world order. Unlike traditional paths to global dominance often marked by military expansion, China has focused on peaceful strategies driven by economic policies, infrastructure development, and international cooperation. Through initiatives like the Belt and Road Initiative (BRI), China has fostered connectivity and trade, enabling developing nations to integrate into the global economy while creating new markets for Chinese goods and investments. This economic diplomacy has allowed China to challenge the long-standing hegemony of Western nations, promoting an alternative vision of globalization that prioritizes inclusivity and mutual benefit. As the world witnesses a relative decline in unilateral dominance by any single superpower, China's strategic partnerships across Asia, Africa, and Latin America emphasize a shared approach to growth and development. China's peaceful rise, however, has not been without challenges. Critics argue that its economic dominance could lead to geopolitical tensions and dependencies among partner countries. Nevertheless, China's focus on innovation, green technologies, and digital transformation highlights its commitment to sustainable development. By recalibrating the balance of global power through economic means, China is enabling the emergence of a multipolar world where no single entity dictates international norms. This transition fosters a more diverse and balanced global order, reflecting the aspirations of various nations. As China continues to rise, the world faces opportunities for collaboration and challenges in managing this profound shift in international dynamics. Keywords: China, economic growth, peaceful, multipolar world, global cooperation, power balance.